Selective IgA deficiency with 18q+ and 18q-- karyotypic anomalies. Issue 6 (December 1980) - Lewkonia, R M; Lin, C C; Haslam, R H
Abstract : A case is described of selective immunoglobulin A deficiency in association with an 18q+ anomaly, apparently the result of a break at 18q23 and a de novo translocation. The presentation is compared with the phenotypic and immunological features in an IgA deficient 18q-- patient. The findings in these two patients suggest that gene(s) concerned with regulation of IgA synthesis are located on the distal long arm of chromosome 18 between 18q23 and qter.